2016
DOI: 10.1111/mice.12243
|View full text |Cite
|
Sign up to set email alerts
|

The Fast Prefix Coding Algorithm (FPCA) for 3D Pavement Surface Data Compression

Abstract: The enormous data inflow during three‐dimensional (3D) pavement surface data collection requires an efficient compression system for 3D data. However, with respect to the phase of lossless encoding, the commonly used Huffman Coding is inefficient in terms of speed and memory usage for encoding 3D pavement surfaces. The Fast Prefix Coding Algorithm (FPCA) is proposed in the article as an effective substitute of Huffman Coding at the stage of lossless encoding. It is demonstrated in the article that the FPCA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Deep CNN, as one kind of DNN, has presented its great potential for multiscale and multilevel image processing. First, both gray and colorful images, even Red‐Green‐Blue (RGB)‐depth images could be mixed as the input of DNNs (Jahanshahi et al., ; Jahanshahi and Masri, ; Ouyang and Xu, ; Huang et al., ; Jiang and Tsai, ; Zhang et al., ; Guldur Erkal and Hajjar, ; Zhang and Wang, ). On the other side, both local and global features could be learned by DNNs, leading to multilevel outputs, including image level, grid level, and pixel level.…”
Section: Related Researchmentioning
confidence: 99%
“…Deep CNN, as one kind of DNN, has presented its great potential for multiscale and multilevel image processing. First, both gray and colorful images, even Red‐Green‐Blue (RGB)‐depth images could be mixed as the input of DNNs (Jahanshahi et al., ; Jahanshahi and Masri, ; Ouyang and Xu, ; Huang et al., ; Jiang and Tsai, ; Zhang et al., ; Guldur Erkal and Hajjar, ; Zhang and Wang, ). On the other side, both local and global features could be learned by DNNs, leading to multilevel outputs, including image level, grid level, and pixel level.…”
Section: Related Researchmentioning
confidence: 99%
“…Adeli and Kumar (1999) developed algorithms using parallel and distributed computing techniques that take advantage of the concurrency of multiple processors to execute processes at the same time. Zhang and Wang (2017) used parallel computing techniques in the process of encoding full-lane width pavement in 3D and at 1 mm resolution with an up-to-date desktop computer at 150 MPH and even higher speed. Yu et al (2018) harnessed the parallel computing to optimize the method for prediction of bus arrival time and applied it to real-time prediction that achieved good results.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang and Wang. [8] proposed a lossless algorithm to compress 3D surfaces and showed that the compression ratio can be even higher than 100 for smooth 3D surfaces.…”
Section: Introductionmentioning
confidence: 99%